2007
DOI: 10.1038/sj.mp.4001971
|View full text |Cite
|
Sign up to set email alerts
|

A role for SC35 and hnRNPA1 in the determination of amyloid precursor protein isoforms

Abstract: The b-amyloid peptide (Ab) that accumulates in senile plaques in Alzheimer's disease is formed by cleavage of the amyloid precursor protein (APP). The APP gene has several intronic Alu elements inserted in either the sense or antisense orientation. In this study, we demonstrate that binding of SC35 and hnRNPA1 to Alu elements on either side of exon 7 in the transcribed pre-mRNA is involved in alternative splicing of APP exons 7 and 8. Neuronal cells transfected with the full-length form of APP secrete higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 47 publications
3
69
0
1
Order By: Relevance
“…In addition, our experiments using siRNA directed against CaMK IV strengthened the hypothesis of an alternative splicing mechanism in which CaMK IV plays a major role. Interestingly, a recent publication demonstrated the fundamental role of two neuronal splicing factors, hnRNPA1 and SC35, in the regulation of exon 7 (containing KPI domain) skipping during APP pre-mRNA maturation (Donev et al, 2007). By lowering the expression of one or both factors, they reported an increase in KPI-APP expression with a subsequent elevated A␤ production in neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our experiments using siRNA directed against CaMK IV strengthened the hypothesis of an alternative splicing mechanism in which CaMK IV plays a major role. Interestingly, a recent publication demonstrated the fundamental role of two neuronal splicing factors, hnRNPA1 and SC35, in the regulation of exon 7 (containing KPI domain) skipping during APP pre-mRNA maturation (Donev et al, 2007). By lowering the expression of one or both factors, they reported an increase in KPI-APP expression with a subsequent elevated A␤ production in neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results strengthen the hypothesis of the involvement of CaMK IV in extrasynaptic NMDAR activation-induced KPI-APP mRNA expression through the regulation of alternative splicing of APP pre-mRNA. By siRNA knockdown experiments, it was recently shown that heterogeneous nuclear ribonucleoprotein (hnRNP) A1 and SC35 are major factors involved in skipping of exon 7 (corresponding to KPI domain) of APP pre-mRNA (Donev et al, 2007). hnRNP proteins were initially described as a splicing repressor by directly antagonizing the recognition of splice sites (for review, see Martinez-Contreras et al, 2007).…”
Section: Extrasynaptic Nmdar Activation Regulates Splicing Of App Mrnmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing body of evidence points towards steroid hormones as potential modulators of alternative splicing. Oestrogen can bring about the upregulation of important regulators for splicing, such as SR-protein (SC35) and hnRNPA1 [103] and can regulate transcription and mRNA splicing directly though CAPER molecules [104]. Oestrogen and other steroid hormones can also affect the ratio of D 2S and D 2L dopamine receptor variants in various target cells both in vitro and in vivo, without affecting total receptor mRNA expression, suggesting that steroid sex hormones exert their effects, at least in part, at the level of alternative splicing [105,106].…”
Section: Mechanisms Of Alternative Splicing Of Gpcrsmentioning
confidence: 99%
“…Donev [6] developed a novel atomic force microscopy based approach for identifying protein binding sites in nucleic acids. Furthermore, he discovered a mechanism controlling alternative splicing of the Amyloid Precursor Protein (APP) mRNA and secretion of β-amyloid peptide by cultured neurons [7]. In 2003 Dr. Donev moved to the School of Medicine, Cardiff University where he gained extensive experience in innate immunity.…”
Section: Introductionmentioning
confidence: 99%